Characterization of polysaccharide antigens of Streptococcus mutans B13 grown under various conditions. - Linzer, R (Infect Immun, 1984)
Bacteria may respond to changes in their environment by varying the synthesis of surface components. This study examined the effects of various culture conditions on two wall polysaccharides of Streptococcus mutans B13 (serotype d): serotype d antigen, a galactose-glucose polymer, and RGP antigen, a rhamnose-glucose polymer. Cells were grown in a chemostat at various dilution rates (D) and pH values, including D = 0.05, 0.1, and 0.5 h-1 at pH 6.0 and D = 0.1 h-1 at pH 5.5, 6.0, 6.5, and 7.5. The cells were examined for protein and carbohydrate content by colorimetric assays and gas-liquid chromatography. Rantz-Randall extracts (120 degrees C, 30 min) and M-1 N-acetylmuramidase digests were prepared and examined for the presence of specific antigens by agar gel diffusion and quantitative precipitation assays. Cell preparations did not vary significantly with respect to total protein or carbohydrate content; however, cells grown at D = 0.1 h-1 and pH 7.5 had a significantly higher rhamnose content than did the other preparations. Rapidly growing cultures appeared to be more resistant to M-1 N-acetylmuramidase digestion than did slower-growing cultures. Agar gel diffusion studies demonstrated that both serotype d and RGP antigens were present in all samples, although significantly less RGP antigen was noted in the pH 7.5 culture. These observations were confirmed by quantitative precipitation assays. M-1 N-acetylmuramidase digests of the pH 7.5 culture were lacking in RGP precipitation activity although RGP inhibition activity was demonstrated. The data suggest that the cell content of serotype d antigen was relatively constant under the growth conditions tested, whereas the synthesis of RGP antigen was modified under conditions of high pH. IMAGES: